Culture and entrepreneurial dynamics in middle-income countries: unlocking opportunities in the startup scene. (2023)
The main objective of this study is to investigate how the cultural value placed on individual success, self-sufficiency, and individual responsibility, influence the startup rate across middle-income countries. We found a positive relationship between this values and startup rates.